Mental health morbidities and their correlates among the adolescents in kamrup (Metro), Assam: A school-based study - Anku M Saikia; Hemen Das; Vinoth Rajendran (Wolters Kluwer Medknow Publications, 2023)
Background: India has the largest adolescent population worldwide, and among this group, mental health issues account for 16% of the total global burden of disease and injury. Disturbingly, approximately half of these health conditions manifest before the age of 14 years. To assess the prevalence of depression, anxiety, and stress along with its correlates among the adolescents in the schools of Kamrup (Metro) district, Assam. Methods and Material: This cross-sectional study was conducted in 10 randomly selected high schools in the study area among the adolescents selected from 8th to 10th standards in the age group of 14 to 17 years. A pre-designed, pre-tested interview schedule, the modified Kuppuswamy scale, and 'Depression Anxiety Stress Scale-21 Items' (DASS 21) questionnaire were used for data collection. Results: The mean ± 2SD age of the adolescents was 14.74 ± 1.58 years. Among the adolescents, the overall prevalence of depression, anxiety, and stress was found to be 22.2%, 24.4%, and 6.9%, respectively. Conclusions: The occurrence of mental health morbidities among adolescents is notably widespread, yet researchers have largely overlooked this aspect. This underscores the need for comprehensive investigations into the factors that contribute to these mental health issues.